Comparative Effectiveness of Mineral Trioxide Aggregate (MTA) and Calcium Hydroxide in Partial Biopulpectomies of Mus musculus teeth - Olivera-Acuña , Williams; Hinostroza, Daniel Felen; Escajadillo, Jane Hospinal P.; Fernández, Jorge Calderón; Gonzales, James Anticona; Sedano, Edwin Tovar; Ninahuanca, Jordan (Revista de Ciências Agroveterinárias, 2025)
This study compared the effectiveness of Calcium Hydroxide and Mineral Trioxide Aggregate (MTA) in partial biopulpectomies of Mus musculus teeth. A total of 16 rats (n=8 per group) were used, evaluating inflammation (levels 1: very mild to 4: severe), necrosis, and granulation tissue formation at 7 and 21 days. Using non-parametric tests (Fisher’s exact test, McNemar, Wilcoxon, and Mann-Whitney), no significant intergroup differences were found in inflammation (p > 0.05 at 7 days; p > 0.05 at 21 days) or necrosis (p > 0.05 at 7 days; p > 0.05 at 21 days). However, MTA exhibited superior clinical trends, achieving complete necrosis resolution (0% vs. 25% in Calcium Hydroxide) and granulation tissue formation (100% vs. 87.5%) at 21 days, with significant intragroup reductions in granulation (p < 0.05 vs. p < 0.05). The wide confidence intervals (e.g., necrosis in MTA at 21 days: 0.0–36.9%) and moderate effect sizes (φ=0.42; r=-0.45) reflected sample size limitations, highlighting the need for larger studies. While both materials demonstrated biocompatibility, MTA emerges as a preferred option in contexts prioritizing comprehensive tissue repair, supported by its profile without post-operative complications. These findings provide preliminary evidence to guide future multidisciplinary investigations with greater statistical power.